2011
DOI: 10.3109/17453674.2011.606074
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment of distal radius fractures in Reykjavik, Iceland, in 2004

Abstract: Background and purposeRecent literature suggests that the incidence and treatment modalities of distal radius fractures have been changing over the past 2 decades in the developed world. We examined the epidemiology of adult distal radius fractures in Iceland in 2004 and compared it with an Icelandic study from 1985 and other studies.MethodsA retrospective study of the epidemiology, classification, and treatment of distal radius fractures in Reykjavik residents aged 16 and older in 2004 was conducted by analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 14 publications
6
27
3
8
Order By: Relevance
“…increase levelled off around the millennium. 25,[30][31][32][33] In our data, we found a slow rise in the incidence of fractures in the adult population between 2005 and 2010, but the levels did not reach those reported from the 1980s. 28 Some of the variation in incidence in our study may be explained by the extreme weather conditions experienced during the Swedish winter.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…increase levelled off around the millennium. 25,[30][31][32][33] In our data, we found a slow rise in the incidence of fractures in the adult population between 2005 and 2010, but the levels did not reach those reported from the 1980s. 28 Some of the variation in incidence in our study may be explained by the extreme weather conditions experienced during the Swedish winter.…”
Section: Discussioncontrasting
confidence: 78%
“…34 The incidence rates in our study are similar to those reported by other recent epidemiological studies from Scandinavia. 23,30,32 The extent of osteoporosis in the population is considerable, and pharmacological prophylaxis has been used. 35 It is possible that the effect of such medication might be reflected in the slight decrease in the incidence of fractures of the distal radius reported at the start of the 21st century, but this is not supported by the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Many of the accidents causing these low energy fractures occur as an individual tries to stop a fall with a dorsally outstretched hand. Evidence has also shown that distal radius fractures seem to occur more often in cognitively intact individuals as opposed to those with significant dementia.…”
Section: Elderly Incidencementioning
confidence: 99%
“…Supporting this theory, the use of hip pads was significantly associated with a lower risk of distal radial fracture and glenohumeral dislocation. In general, distal radial fracture frequently occurs when the hands impact the ground after falling,15 and glenohumeral dislocation is mostly caused by the force of shoulder abduction, extension and external rotation 16 17. Snowboarders falling backward are easily assumed to reflexively take these actions to defend themselves.…”
Section: Discussionmentioning
confidence: 99%